ANALISIS PENDAPATAN USAHA TANI TAMBAK IKAN BANDENG (Studi Kasus di Desa Segoro Tambak, Kecamatan Sedati Kabupaten Sidoarjo, Jawa Timur) - Sriyanti, Kornelia; Humaidi, Faisol (Fakultas Pertanian Universitas Wijaya Putra, 2024)
This research aims to determine the income of milkfish pond farming in Tampinna Village, East Luwu Regency. The population in this study was taken randomly, namely 20 respondents. Data analysis used quantitative data analysis using the formula TC = FC + VC, TR + P.Q, Pd = TR - TC. The research results show that the income from milkfish farming in Tampinna Village is profitable. Where, the average production produced by milkfish pond farmers is 3,450.45 kg/year per cycle with an income of IDR 26,870,730/harvest in one cycle. keywords: Milkfish Pond Income Analysis.